Analysis of community composition of biofilms in a submerged filter system for the removal of ammonia and phenol from industrial wastewater. (20th January 2006) - Cortés-Lorenzo, C.; Molina-Muñoz, M.L.; Gómez-Villalba, B.; Vilchez, R.; Ramos, A.; Rodelas, B.; Hontoria, E.; González-López, J.
Abstract : The bacterial diversity of a submerged filter, used for the removal of ammonia and phenol from an industrial wastewater with high salinity, was studied by a cultivation-independent approach based on PCR/TGGE (temperature-gradient gel electrophoresis). The wastewater treatment plant (laboratory scale) combined the nitrification and denitrification processes and consisted of two separated columns (one anoxic and one aerated) connected through a valve. The spatial diversity of bacterial communities in the plant biofilms was analysed by taking samples at four different heights in the system. TGGE profiles of PCR-amplified sequences of the 16 S rRNA gene (V3-hypervariable region) showed significant variations of the bacterial diversity, mainly depending on the concentration of O2 along the system. Several bands separated by TGGE were reamplified and sequenced, in order to explore the composition of the microbial communities in the biofilms. Most of the sequenced bands (10 out of 13) were closely related to the 16 S rRNA gene of marine α-proteobacteria, mainly grouping in the periphery of the genus Roseobacter . Other sequences were related to those of γ-proteobacteria, the nitrite oxidizer Nitrospira marina and anaerobic phenol-degrading bacteria of the Desulfobacteraceae.